The relationship between stingless bee and native plants studies - Wan Saiful Nizam Wan Mohamad,; Khalilah Hassan,; Ayub Awang,; Mohammad Rusdi Mohd Nasir,; Nur Hafizah Ramle,; Noorliyana Ramlee,; Hafizah Pulli, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
In the past decade, the benefits of stingless bee honey as an anticancer agent has increased in demand in Malaysia. Despite the increasing demand, the quality produced highly depends on a certain plant, Ixora spp. The practice of planting design in landscape development only by considering the aesthetic values leads to the poor productivity of stingless bee honey. Therefore, this review focuses on the suitability of native plants used in landscapes designed for stingless bees. This study employed thematic analysis related to the issues between native plants, stingless bee and landscape development. Based on the assessment, literature on stingless bees discussed issues related to its habitat in the tropical rain forest, the behaviour of finding food, characteristics of its honey and the benefits of consuming the honey. Meanwhile, studies on native plant demonstrated the use of plants in providing food and habitat to the local insects which contribute to the continuity of the species. As a conclusion, the quality of honey is dependent on the relationship between stingless bees and native plants. Hence, the native plants can be potentially used in planting design for the improvement of stingless bee honey production.